KETERKAITAN ANTARA MODAL SOSIAL DENGAN EFISIENSI KELEMBAGAAN PADA KOPERASI PONDOK PESANTREN SIDOGIRI, PASURUAN - FARAHDILLA KUTSIYAH; AGOES KAMAROELLAH; UMMU KALSUM (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
Sidogiri Islamic Boarding School is one of the oldest Islamic boarding schools and is capable of being independent in its operational activities by having very rich resources and this institution is also an example of success in developing Islamic economics. The deﬁnition of "institution" in this article is how the rules are implemented in the pesantren's economic activities that are deeply tied to the social capital that they have. This study uses a case study qualitative approach. Data collection through observation, documentation and in-depth interviews. The results of the study show that social capital that is embedded in the pesantren environment can reduce transaction costs so that the institutional of Sidogiri Islamic Boarding School cooperative is more eﬃcient. Network can reduce the cost of information, negotiation, coordination and supervision. Norms can decrease the occurrence of irregularities and the existence of trust. Shared vision can facilitate coordination and increase motivation. It is recommended that the application of social capital in the management of the Sidogiri kopontren be able to be transferred some other pesantren that are still lagging behind in economic development so that they are able to be independent and can help the economic problems of the community.